2010
DOI: 10.1021/jf904407x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anthocyanin-Rich Extract from Black Rice (Oryza sativa L. Japonica) on Chronically Alcohol-Induced Liver Damage in Rats

Abstract: The study evaluated the protective effect of anthocyanin-rich extract from black rice (AEBR) on chronic ethanol-induced biochemical changes in male Wistar rats. Administration of ethanol (3.7 g/kg/day) to Wistar rats for 45 days induced liver damage with a significant increase (P < 0.05) of aspartate transaminase (AST), alanine transaminase (ALT), gamma glutamyl transferase (GGT) in the serum and the hepatic malondialdehyde (MDA) level. In contrast, administration of AEBR (500 mg/kg) along with alcohol signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 33 publications
(38 reference statements)
8
95
0
Order By: Relevance
“…Hom-Dang extract effectively normalized the levels of hepatic transaminases GPT and GOT in paracetamol-treated mice by restoring the glutathione system. Our findings support another study where an anthocyanin-rich extract from black rice (O. sativa L. Japonica) had beneficial effects on alcoholinduced liver damage in rats (Hou et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Hom-Dang extract effectively normalized the levels of hepatic transaminases GPT and GOT in paracetamol-treated mice by restoring the glutathione system. Our findings support another study where an anthocyanin-rich extract from black rice (O. sativa L. Japonica) had beneficial effects on alcoholinduced liver damage in rats (Hou et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The body weights in ethanol treated group rats were found to be significantly (P≤0.05) reduced as compared to the control, which is similar to the previous reports (Lieber, 1994;Hou et al, 2010); the reason may be due to malabsorption and food intake loss (Lieber, 1994). The excessive alcohol ingestion disturbs the metabolism of most nutrients in diet resulting in malnutrition (Lieber, 2000).…”
Section: Resultssupporting
confidence: 84%
“…There are several studies, in normal cells and tissues, in which it was demonstrated that anthocyanins, probably involving some protein kinases, modulate the activity of some GSHdependent enzymes, thus ameliorating the antioxidant response (Hou et al, 2010;Suda et al, 2008;Veigas et al, 2008). GSSG formed intracellularly is continuously reduced to GSH by the activity of GR.…”
Section: Gsh Role In Apoptosismentioning
confidence: 99%